For the anthropology to the creativity - Guerci de Siufi, Beatriz; Pérez del Viso de Palou, Rosa (Anales de Psicología / Annals of Psychology, 2010)
After acknowledging that inquiring is a specifically human ability, a question is understood as a cognotivist tool that allows the elimi-nation of an initial state of darkness and latency in order to reach the construction of clear and sensitive knowledge to be communicated. In this passage a four element structure can be identified: reality, subject, language and social relations, which are dynamically determined. This interaction can be transposed to the questioning configuration, provided there is a subject that makes questions, from the aptitudinal and attitudinal, to a reality which is presented but on which he takes part, being able to express himself and to express it in a language which is the context product where it is articulated. In this work it is proposed a development of those elements from the Philosophical Anthropology, emphasizing that the acceptance of a com-plex world is important for the construction of the subject himself. Also we try to move forwards in the special features that such constructions reach when the search goes to the scientific and philosophical inquiry, that from their more basic levels need a creative spirit.